Miniature Soft Electromagnetic Actuators for Robotic Applications. (5th March 2018) - Do, Thanh Nho; Phan, Hung; Nguyen, Thuc‐Quyen; Visell, Yon
Abstract: Electromagnetic actuators (EMAs) serve the majority of motion control needs in fields ranging from industrial robotics to automotive systems and biomedical devices, due to their unmatched combination of speed, precision, force, and scalability. This paper describes the design and fabrication of miniature soft EMAs that operate based on the Lorentz force principle. The actuators are fabricated from silicone polymer, liquid metal (LM) alloy (eutectic gallium indium, EGaIn), and magnetic (NdFeB) powder. They are small, intrinsically deformable, and can be fabricated using simple techniques. The central elements of the actuators are fine, 3D helical coil conductors, which are used as electromagnetic inductors. The coils are formed from stretchable filaments that are filled with a LM alloy. To achieve high power densities, the filaments themselves may be fabricated from colloids of EGaIn microdroplets in a silicone polymer matrix, allowing them to dissipate heat and accommodate high currents, and thus high forces. Millimeter‐scale cylindrical actuators are demonstrated for linear high frequency motion and articulated devices for bending motion. These actuators are applied in a vibrotactile feedback display and in a miniature soft robotic gripper. Abstract : Miniature soft electromagnetic actuators are presented for applications in robotics. These devices are based on fine helical inductors fabricated from silicone polymer colloids, liquid metal alloy (EGaIn), and magnetic (NdFeB) powder. They are small, intrinsically deformable, and can be fabricated using simple techniques. Actuators are demonstrated for high frequency motion, including a tactile display and miniature soft robotic gripper.